Stardust monuments : the saving and selling of Hollywood - Trope, Alison (Interfaces, studies in visual culture., 2011)
Hollywood is placeless, timeless, and iconic, a key fabricator and forger of American cultural myths and stories. How, then, will the history of Hollywood be written?